Analisis Elemen Kunci Brand Equity Citilink pada Wilayah Tangerang: Evaluasi Mendalam dalam Konteks Industri Penerbangan - Asep Rana Purwadi; Kharisma Dewi Yasinta; Dini Yerinda; Rafelia Aurelien; Muhammad Abdullah (Jurnal Manajemen Dirgantara, 2024)
This study aims to analyze the brand equity of Citilink in the Tangerang region, focusing on four key dimensions: brand awareness, brand association, brand perceived quality, and brand loyalty. Brand equity is a crucial factor influencing consumer decisions when selecting a brand. A mixed-method approach was employed for this research. The qualitative aspect involved descriptive analysis to systematically describe phenomena related to brand awareness, brand perceived quality, and brand loyalty. The quantitative approach tested hypotheses concerning brand association using the Cochran Q test compared to the Chi-Square table. The sample comprised 96 airline service users in Tangerang, selected through purposive sampling, with criteria including residence in Tangerang, age of at least 17 years, and having used airline services within the past three months. The findings indicate that Citilink enjoys very high brand awareness, with nearly all respondents recognizing the brand. Citilink's brand association is generally positive, particularly concerning affordable ticket prices and friendly service. The brand’s perceived quality is rated positively by the majority, covering aspects such as comfort, safety, and customer service. Additionally, most Citilink customers exhibit high loyalty and satisfaction with the services provided. The study recommends that future research be conducted across various regions in Indonesia to compare Citilink's brand equity with other airlines in different regional contexts. Further in-depth studies on brand associations, including the impact of price, service, and promotions on consumer perceptions, are suggested. Future research should also evaluate the effects of changes in logo design and visual elements on brand awareness and brand association. Additionally, qualitative methods such as in-depth interviews or focus group discussions are recommended to gain deeper insights into customer satisfaction and dissatisfaction. Evaluating pricing and promotional strategies, along with the impact of social and digital media on brand equity, will also be crucial for future studies.